Dynamics of somatic cell count and intramammary infection in lactating dairy cows - Sumon, SM Mostafizur Rahaman; Parvin, Mst Sonia; Ehsan, Md Amimul; Islam, Md Taohidul (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The influence of intramammary infection (IMI) and types of bacteria was assessed on somatic cell count (SCC) in dairy cows’ milk with respect to breed, age, parity, stage of lactation, milk production, and mammary quarter location. Materials and methods: After recording data in a structured questionnaire, 360 samples of quarter milk were collected. The samples were subjected to SCC and isolation and identification of bacteria. The data were analyzed to find out the significant influence of independent factors on SCC and IMI. Results: The infected quarters had a significantly higher mean SCC (210.52 × 103 cells/ml) compared to uninfected ones (32.72 × 103 cells/ml). The mean SCC was the highest for IMI with Enterobacterspp. (338.00 × 103 cells/ml) followed by Bacillus spp. (319.20 × 103 cells/ml), coagulase-negative Staphylococci (CNS) (268.17 × 103 cells/ml), Staphylococcus aureus (218.31 × 103 cells/ ml), and Escherichia coli (200.75 × 103 cells/ml) and the lowest for Pseudomonas aeruginosa (66.33 × 103 cells/ml). Milk of rear quarters had a significantly higher SCC than the front quarters. SCC increased with increasing age, parity, and lactation stage regardless of whether cows are infected or not. The IMI was more prevalent in rear quarters (42.2%) and cows at early (≤7 days) lactation (100.0%). Cows having a parity of ≥5 and crossbred and high yielding (>5 l) cows had also a higher rate of IMI of 38.2%, 36.7%, and 38.2%, respectively. Conclusion: The IMI and type of bacteria were the principal factors for SCC variation. Besides, mammary quarter location, age, and parity should be taken into consideration during the interpretation of SCC. Adv. Vet. Anim. Res., 7(2): 314-319, June 2020